Weed Management Guide for Florida Lawns - J. Bryan Unruh; Laurie Trenholm; Erin Harlow; Ramon G. Leon (EDIS)
Weeds can be defined as unwanted plants or plants growing out of place. Proper identification and some understanding of how and why weeds are present in a lawn are important when selecting the best control strategy. Knowing if weeds were previously present in an area also helps homeowners prepare control measures in the future. Weed control should be a carefully planned and coordinated program. https://edis.ifas.ufl.edu/ep141